ByzRev 07.2025.057: Caroline Macé (ed.), Organising a Literary Corpus in the Middle Ages.: The Corpus Nazianzenum and the Corpus Dionysiacum. Turnhout: Brepols 2024. - Roelli, Philipp (The Byzantine Review, 2025)
Caroline Macé (ed.), Organising a Literary Corpus in the Middle Ages. The Corpus Nazianzenum and the Corpus Dionysiacum. Turnhout: Brepols 2024. 699 pp. – 978-2-503-61096-2